Sociodemographic and clinical profile of patients treated with oral anticoagulants - Thaisa Remigio Figueirêdo; Hirla Vanessa Soares de Araújo; Tâmara Silva; Maria Mariana Barros Melo da Silveira; Christefany Régia Brazc Costa; Simone Maria Muniz da Silva Bezerra (Rev Rene)
Objective: to describe the sociodemographic and clinical profile of patients treated with oral anticoagulants. Methods: cross-sectional study, conducted in an anticoagulation outpatient facility of a teaching hospital which is reference in cardiology. One evaluated 222 patients, through individual interviews using a structured questionnaire. Data were analyzed using descriptive statistics. Results: the participants were characterized predominantly by the following characteristics: female (64.4%); brown (57.2%); low education (68.0%); poor (67.1%); most with values of the International Normalized Ratio outside the therapeutic range (57.2%); associated comorbidities; and prolonged treatment time (65.8%). Conclusion: it was evident a predominantly female group, with low socioeconomic status, associated comorbidities and prolonged treatment time with oral anticoagulants. It constitutes the biggest part of a vulnerable group whose characteristics can affect the quality of the treatment, and with characteristics related to the particular culture of northeastern Brazil, not found in anticoagulation outpatient facilities in other regions of the country.